Assessing adherence to treatment guidelines and complications among atrial fibrillation patients in the United Arab Emirates - Ayash, Bayan; Malaeb, Diana; Hallit, Souheil; Hosseini, Hassan (Frontiers in Cardiovascular Medicine, 2024)
Background Atrial fibrillation (AF), a potential trigger for stroke development, is considered a modifiable condition that can halt complications, decrease mortality, and prevent morbidity. The CHA₂DS₂-VASc and HAS-BLED scores are categorized as risk assessment tools used to estimate the risk of thrombosis development and assess major bleeding among atrial fibrillation patients. Objectives Our study aims to assess the adherence to post-discharge treatment recommendations according to CHA₂DS₂-VASc score risk group and evaluate the impact of CHA₂DS₂-VASc score and HAS-BLED score risk categories on death, length of hospital stay, complications, and hospital readmission among United Arab Emirates (UAE) patients. Methods This was a multicenter retrospective study conducted from November 2022 to April 2023 in the United Arab Emirates. Medical charts for AF patients were assessed for possible enrolment in the study. Results A total number of 400 patients were included with a mean age of 55 (±14.5) years. The majority were females (67.8%), and most had high CHA₂DS₂-VASc and HAS-BLED scores (60% and 57.3%, respectively). Our study showed that adherence to treatment recommendations upon discharge was 71.8%. The bivariate analysis showed that patients with a high CHA₂DS₂-VASc score had a significantly higher risk of death (p-value of 0.001), hospital readmission (p-value of 0.007), and complications (p-value of 0.044) vs. the low and moderate risk group with a p-value of <0.05. Furthermore, our findings showed that the risk of death (0.001), complications (0.057), and mean hospital stay (0.003) were significantly higher in the high HAS-BLED risk score compared to both the low- and moderate-risk categories. Hospital stay was significantly higher in CHA₂DS₂-VASc and HAS-BLED high-risk score categories compared to the low-risk score category with a p-value of <0.001. Conclusion Our study concluded that the adherence to treatment guidelines in atrial fibrillation patients was high and showed that patients received the most effective and patient-centered treatment. In addition, our study concluded that the risk of complications and mortality was higher in high-risk category patients.